Positive Pressure Ventilation Treatment Based on Daytime and Night-time Titration in Patients with Obesity Hypoventilation Syndrome: A Randomized Controlled Trial - Amra, Babak; Ghasemi, Marzieh; Soltaninejad, Forogh; Salmasi, Mehrzad (Sleep Science, 2023)
Objectives The aim of the present study was to investigate the improvements of gas exchange and excessive daytime sleepiness in patients with obesity hypoventilation syndrome (OHS) in daytime and night-time split polysomnography (DSPSG and NSPSG).Materials and Methods In the present randomized controlled trial, patients with OHS were enrolled in two DSPSG (51 patients) and NSPSG (50 patients) groups in the Bamdad respiratory and sleep research center in Isfahan, Iran. In both groups, the diagnostic polysomnography (PSG) and titration were conducted in one session according to the guidelines of NSPSG. SpO2, PaCO2, and the Epworth Sleepiness Scale (ESS), were measured initially and 12 weeks after treatment. Furthermore, the PSG parameters and the type of treatments for the two groups were recorded and analyzed.Results A total of 101 OHS patients (age: 62.02 ± 12.4 year old; 61 females [60.4%]) were evaluated. There were no significant differences regarding BMI, gender, and AHI between groups (p > 0.05). Primary SpO2, PaCO2, and ESS were not significantly different between the two groups. After 12 weeks of treatment by continuous positive airway pressure (CPAP) or bi-level positive airway pressure (BiPAP), there were significant improvement of SpO2, PaCO2, and ESS score (p < 0.001). The amount of change of these variables was not different between groups. Among all variables, only the lower SpO2 and higher PaCO2 were associated with response to BiPAP.Discussion There were no significant differences in the number of changes of SpO2, PaCO2, and ESS by treatment in the DSPSG and NSPSG groups. Therefore, DSPSG may be considered as a valuable alternative method for the diagnosis and titration in OHS patients.Clinical Trials IRCT20170512033930N2
Keywords: continuous positive airway pressure; obesity hypoventilation syndrome; noninvasive ventilation; polysomnography; obesity